Eksperimen Model Pembelajaran Core (Connecting Organizing Reflecting Extending) Dan Konvensional Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa Kelas VIII SMP Negeri 3 Sawit Semester Genap Tahun Ajaran 2015/2016 - Puspitasari, Linda; , Dr. Sumardi, M. Si (2016)
ABSTRACT Linda Puspitasari / A410122009. Experiments Learning Model CORE (Connecting Organizing Reflecting Extending) and Conventional Against Judging from the Mathematics Learning Outcomes Student Motivation Kela VIII SMP Negeri 3 Oil Semester Academic Year 2015 / 2016.Skripsi, the Faculty of Education, University of Muhammadiyah Surakarta. September, 2016. Abstract: This study aims to determine: (1) the effect of the use of learning model CORE with a contextual approach to the learning outcomes, (2) influence student motivation toward student learning outcomes, (3) whether there is an interaction model of learning and student motivation for learning outcomes math students. This study was an experimental study. The population in this study all students of class VIII SMP Negeri 3 Sawit the academic year 2015/2016. Samples from this study, taken as many as two classes, namely for the experimental class and control class. The sampling technique is done by random cluster sampling technique. Data collection method used is the method of test and questionnaire as the principal methods and documentation as an auxiliary method. The analysis technique used is the analysis of variance of two different cell previously performed using methods Lilliefors normality test and homogeneity test using Bartlett method. Based on the research results show that: (1) the use of models in the experimental group showed a mean of 79.18, while the control group showed 67.31. These results indicate that there are differences in the use of CORE learning model with a contextual approach to student learning, (2) categories of student motivation low category with a value of 54.38, the category of student motivation being categorized with a value of 63, while the high category 64.68 (3) there is no interaction between the use of models of learning and students' motivation to learn math results. It is based on the results of data analysis has been done, the value of FAB <F table so that it can be concluded that there is no interaction between the model and the model pemebelajaran pemebelajaran CORE conventional in terms of students' motivation high, medium and low math on learning outcomes. Keywords: CORE, student motivation, contextual approach.